Bioelectrical impedance vectors analysis (BIVA) in older adults according to level of physical activity and muscle strength: a comparison of classic and specific approaches - Rabelo, Ismael Figueiredo; Farrell, Shannon; Reid, Kieran F.; Dos Santos, Vanessa Ribeiro; Antunes, Melissa; Batista, Vitor Cabrera; Bauermann-Vieira, Andreia; Gobbo, Luís Alberto (Frontiers in Aging, 2025)
IndroductionBioelectrical Impedance Analysis (BIA) is a widely used method to assess body composition. Traditional BIA models use predictive equations without considering individual characteristics such as age, sex, and activity level. Classic Bioelectrical Impedance Vector Analysis (BIVA) standardizes raw BIA data by height, while specific BIVA (spBIVA) normalizes by body segment areas and lengths, offering a potentially more accurate assessment. With aging populations, there is growing interest in assessing age‐related body composition changes ‐ especially sarcopenia, characterized by reduced muscle mass and function. While BIVA is promising for such assessments, limited studies compare classic and specific BIVA approaches in older adults based on physical activity and muscle strength. Thus, the objective of the study is to compare classic and specific BIVA values in older adults according to their physical activity level and muscle strength.MethodsThis cross‐sectional study involved 187 community‐dwelling older adults (143 women and 44 men, ≥60 years), recruited via public advertisements. Exclusion criteria included medical conditions affecting muscle mass. The Assessments included: Anthropometry (weight, height, BMI, waist, arm and calf circumferences); BIA (resistance ‐ R, reactance ‐ Xc, and phase angle ‐ PhA), measured using a 50 kHz analyzer (classic BIVA was normalized by height and specific BIVA by segmental area/length using upper arm); physical activity (measured using the Baecke Habitual Physical Activity Questionnaire); muscle strength (measured by handgrip dynamometry, cut‐off values <27 kg for men and <16 kg for women indicated low strength). For the statistical analyses, differences in BIVA parameters were evaluated using Hotelling’s T2 test and Mahalanobis D distances (p < 0.05).ResultsMen had significantly higher body weight, height, waist circumference, and handgrip strength (p < 0.05). Classic BIVA consistently showed higher values of R and Xc than specific BIVA (differences up to 30%). PhA was higher in men, especially due to lower resistance values. Among women, those with higher physical activity levels had significantly higher PhA, indicating better cellular health. Among men, no significant differences in PhA were observed between activity levels. For muscle strength, stronger men had higher PhA values and significant vector displacement in both models; women did not show significant differences by strength level.Discussion and ConclusionBoth classic and specific BIVA approaches identified differences in impedance parameters related to physical activity and strength. Classic BIVA tends to overestimate resistance and reactance due to height normalization, while specific BIVA, using body segments, may better reflect individual morphological characteristics.